Role of family D ATP-binding cassette transporters (ABCD) in cancer - Hlaváč, Viktor; Souček, Pavel (Biochemical Society transactions, 2015)
ATP-binding cassette (ABC) transporters, belonging to the family D, are expressed in peroxisomes, endoplasmic reticulum or lysosomes. ABCD transporters play a role in transport of lipids, bile acids and vitamin B12 and associate with peroxisomal disorders. ABCD1 performs transport of coenzyme A esters of very-long-chain fatty acids (VLCFA) in peroxisomes and a number of mutations in ABCD1 gene were linked to an X-linked adrenoleucodystrophy (X-ALD). The role of ABCD transporters in tumour growth has not been studied in detail, but there is some evidence that ABCDs levels differ between undifferentiated stem or tumour cells and differentiated cells suggesting a possible link to tumorigenesis. In this mini-review, we discuss the available information about the role of ABCD transporters in cancer.
Keywords: peroxizomy; regulace genové exprese u nádorů; Humans; Disease Progression; Fatty Acids; ABC transportéry; mutace; cancer; lidé; adrenoleukodystrofie; ATP-binding cassette (ABC) transporters; differentiation; mastné kyseliny; peroxisomes; ATP-Binding Cassette Transporters; Neoplasms; progression; nádory; Peroxisomes; Adrenoleukodystrophy; progrese nemoci; Mutation; Gene Expression Regulation, Neoplastic; multigenová rodina; Multigene Family